2014
DOI: 10.1016/j.mib.2013.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of vacuole integrity by bacterial pathogens

Abstract: Many intracellular bacterial pathogens reside within a membrane-bound compartment. The biogenesis of these vacuolar compartments is complex, involving subversion of host cell secretory pathways by bacterial proteins. In recent years it has become clear that disruption of vacuole biogenesis may result in membrane rupture and escape of bacteria into the host cell cytosol. Correct modulation of the host cell cytoskeleton, signalling molecules such as small GTPases and the lipids of the vacuole membrane have all b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 54 publications
0
48
0
Order By: Relevance
“…Many microbial pathogens occupy membrane-bound compartments within infected cells, which often shield them from detection by cytoplasmic sensor or protect them from cytoplasmic antimicrobial factors (Creasey and Isberg, 2014). Pathogens that enter the endocytic network, however, must subvert membrane traffic to avoid transport to degradative intracellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Many microbial pathogens occupy membrane-bound compartments within infected cells, which often shield them from detection by cytoplasmic sensor or protect them from cytoplasmic antimicrobial factors (Creasey and Isberg, 2014). Pathogens that enter the endocytic network, however, must subvert membrane traffic to avoid transport to degradative intracellular compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Although active egress from PVs is occasionally executed by vacuolar pathogens as a strategy to promote intracellular replication, loss of membrane integrity may also occur as an unintended consequence of PV manipulations by resident bacteria (5). Previous studies have demonstrated that PV membrane remodeling and manipulations of PV trafficking by secreted effector proteins can stabilize and destabilize PV membranes (7)(8)(9).…”
Section: Mouse and Human Gbps Colocalize With Galectin-3 At Sterilelymentioning
confidence: 99%
“…For example, some bacterial effectors modify the lipid composition of PVs. As a potential consequence of these lipid modifications, PVs are more likely to rupture when exposed to cytoskeleton motor-dependent mechanical forces (5,6). Although pathogens such as Legionella pneumophila or Salmonella enterica secrete effectors to counteract destabilizing effects of membrane manipulations to maintain the PV as a replicative niche (7)(8)(9), subsets of Legionella-containing vacuoles (LCVs) or Salmonella-containing vacuoles (SCVs) nonetheless fail to maintain their membrane integrity (7,10).…”
mentioning
confidence: 99%
“…Therefore, maintenance of the integrity of bacteria-containing vacuoles is essential for intravacuolar bacterial pathogens. Accordingly, recent studies suggest that intravacuolar bacteria target multiple host components and signaling pathways to maintain the stability of their residing vacuoles (164, 165). …”
Section: Infection Of Macrophages By Intravacuolar Bacteriamentioning
confidence: 99%